Country of origin effect: a study with Brazilian consumers in the luxury market - Maria Gabriela Montanari (FUCAPE Business School, 2018)
This study aimed to verify the extent of the influence of the country of origin in the decision to purchase a product when considering a number of other attributes such as brand, price, warranty and store. In order to verify this country of origin effect, we conducted an empirical study in which 329 Brazilian students used and evaluated three luxury brands from three different nations. From statistical analyses, we concluded that the country of origin is the criterion of minor importance in the purchase decision of a luxury perfume, while the fragrance, the price, and the brand are the most important cues in this purchase. The study provides indications that corroborate the hypothesis that marketing managers should direct their marketing efforts mainly to premium price and symbolism, history and strength of the brand, leaving aside some strategies that emphasize the country of origin of the brand.